When to cryopreserve and when to let it go? A systematic review of priorities in wild animal cryobanking - James Edward Brereton; Sarah Louise Spooner; Susan L. Walker; Andrew Mooney; Philippe Wilson; Gabriela F. Mastromonaco; Elena Hunter; Samuel White (Theriogenology Wild)
With increasing numbers of species threatened with extinction, collecting and conserving living samples is important for the long-term conservation of animal populations. Globally, many cryobanks have been developed to preserve animal tissues for future use in wildlife conservation. However, to date, there has been no attempt to review the purpose, priorities and direction of these cryobanks. A systematic review was undertaken using Web of Science, Scopus, and Google Scholar to determine the most common priorities identified in the cryobanking literature. The types of species being recommended for cryobanking, cell types, and recommended numbers of samples and number of individuals were also recorded for cryobanking efforts. Overall, 13,287 papers were identified, of which 794 were selected for full-text review. For wildlife, the most frequently cited priority was to select based on threat level, with convenience sampling and genetic diversity featuring as the second and third most common priorities. In terms of cell type, sperm featured most frequently in cryobanking literature, potentially due to its ease of use in animal breeding programmes. Somatic cells and stem cells featured more commonly in more recently published literature. Looking ahead, cryobanks should consider their priorities and records to ensure they are collecting samples with a meaningful use for future conservation efforts. Greater collaboration between cryobanks can aid in important sample acquisition and storage and in sharing cryopreservation priorities.